Use of UML 2.1 to model multi-agent systems based on a goal-driven software engineering ontology - Wongthongtham, Pornpit; Dillon, Darshan; Dillon, Tharam S.; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
In this paper, we present the use of UML 2.1 to model multi-agent systems based on a goal-driven software engineering ontology. The lack of an efficient standardized modeling language is evident. The uses of UML and stereotypes UML to model multi-agent systems have been proposed. However, there are still a number of issues with the existing approaches due to inconsistent semantics of the existing UML diagrams and unintuitive and complext notations. UML 2.1 allows representing more complex scenarios and introducing greater details into the modeling process enabling effective capture and representation of multi-agent actions and interactions. UML 2.1 has not only enabled the introduction of a notation for the Ontology based multi-agent systems, but also effective capture and representation of the dynamic processes associated with these Ontology based multi-agent systems.